SOURCE LOCATION USING SINGLE-STATION RECORD - LAZARENKO, M.; HERASYMENKO, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Single-station seismic record has been used for seismic source coordinates (back azimuth and epicentral distance range) evaluation. The initial segments of the seismic record up to 20 seconds duration were used for supervised back-propagated neural network training set compilation. The results for use of various component number and time intervals are presented.